2019
DOI: 10.1186/s12870-019-2189-9
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-mRNA expression profiles and their potential role in cadmium stress response in Brassica napus

Abstract: BackgroundOilseed rape is an excellent candidate for phytoremediation of cadmium (Cd) contaminated soils given its advantages of high biomass, fast growth, moderate metal accumulation, ease of harvesting, and metal tolerance, but the cadmium response pathways in this species (Brassica napus) have yet to be fully elucidated. A combined analysis of miRNA and mRNA expression to infer Cd-induced regulation has not been reported in B. napus.ResultsWe characterized concurrent changes in miRNA and mRNA profiles in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 75 publications
(81 reference statements)
0
26
0
Order By: Relevance
“…We also drew similar conclusions by comparing the distribution of sRNA richness in other plants such as peanuts, rapeseed, tomatoes, and radishes. However, we found that 18 nt sRNAs have the highest richness in wheat [ 31 , 33 , 48 , 49 , 50 ]. Such results indicated that the abundance of sRNAs may only slightly vary between species, regardless of experimental treatment and variety selection.…”
Section: Discussionmentioning
confidence: 99%
“…We also drew similar conclusions by comparing the distribution of sRNA richness in other plants such as peanuts, rapeseed, tomatoes, and radishes. However, we found that 18 nt sRNAs have the highest richness in wheat [ 31 , 33 , 48 , 49 , 50 ]. Such results indicated that the abundance of sRNAs may only slightly vary between species, regardless of experimental treatment and variety selection.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies based on genome-wide transcriptome analysis showed that miR397 could be upregulated by other heavy metal stresses. It was reported that miR397 was upregulated by cadmium (Cd) stress in Brassica napus (Zhou et al 2012;Fu et al 2019), Brassica parachinensis (Zhou et al 2017;Liu et al 2020), and soybeans (Fang et al 2013), as well as by chromium (Cr) in rice (Dubey et al 2020). Gielen et al (2016) found that Cd-exposure led to a decrease in Cu levels in Arabidopsis plants compared with the control (Gielen et al 2016).…”
Section: Heavy Metal Stressmentioning
confidence: 99%
“…Cadmium (Cd), is one of the most prevalent and poisonous elements in agricultural soil, and jeopardizes the environment and human health. Toxicology studies have been undertaken of Cd stress in plants affecting tissue morphological, biochemical and physiological changes, as well as altered gene expressions [3][4][5][6]. The presence of 40 mg L −1 Cd in soil has already been found to affect yield in some crops [7].…”
Section: Introductionmentioning
confidence: 99%